Exploring nursing students' attitudes towards online teaching and learning: challenges and recommendations - Rai, Ajeet Kumar; Sharma, Sushil Kumar; Sharma, Sakshi; Chauhan, Soni; Tiwari, Surya Kant (International Journal Of Community Medicine And Public Health, 2024)
Background: With the increasing integration of technology in education, understanding students' attitudes toward online teaching and learning is crucial for effective educational strategies. The primary objectives were to assess nursing students' attitudes toward online teaching and learning and to explore perceived challenges encountered during online education. Methods: A descriptive cross-sectional survey was conducted among 120 nursing students who experienced online education between March 2020 and February 2022. Data were collected using a self-structured attitude scale and analyzed using descriptive and inferential statistics. Results: The majority of nursing students exhibited positive attitudes towards online teaching and learning, with second-year students displaying the highest mean scores across attitude sub-scales. Challenges identified included internet issues, lack of interaction, and physical problems. Recommendations for improvement included enhancing technological infrastructure, promoting interactive learning experiences, and providing additional support services. Conclusions: Nursing students generally hold positive attitudes towards online teaching and learning, despite facing challenges such as internet connectivity issues and lack of interaction. By addressing these challenges and implementing recommendations for improvement, educational institutions can optimize online education delivery, fostering a positive and conducive learning environment for nursing students in the digital age.